Forest owners’ collective action against the risk of forest fire: a game theoretical approach - Mendes, Américo (2007)
This paper is a follow up on a earlier one (Mendes, 1998) where I proposed a series of models for forest owners associations represented as organisation made up of two groups of strategically interacting players: the forest owners who are members of the association and the board of directors they have elected. The directors decide on the amount of services provided by the association which can be public goods (collective representation of the members, promotion of their common interests, diffusion of general information about forest programmes and best forest management practices, etc.) and private goods and services (silvicultural works preventive of forest fires, technical advice, etc.). The models were set up as games in strategic form with complete information and no payoff uncertainty. Here I pick up the second of, what is called in that previous paper, the "Portuguese" models and extend it in the following directions: - there is payoff risk for the forest owners due to exogenous hazards (forest fires or others); - forest owners can buy private services from the owners which contribute to reduce the losses resulting from those hazards. The main focus in this paper is to derive the comparative static results about the demand of these private services by the forest owners.